Covid-19, Inflation, and Interest Rate: Their Influences on the Jakarta Composite Index - Aryani, Dwi Nita; Maupula, Samuel Williem (Jurnal Minds: Manajemen Ide dan Inspirasi, 2021)
This study aims to determine the effect of inflation, interest rates, and the Covid-19 pandemic condition on the Jakarta Composite Index (JCI) and the difference of the JCI before and after the Large-Scale Social Restrictions (LSSR). Data were collected from January to August 2020. This study evaluates the effect of inflation, interest rate, the Covid-19 Pandemic on the JCI by the t-test and regression, while the Wilcoxon Test tested the JCI before and after LSSR. The results revealed that inflation, interest rates, and the Covid-19 pandemic partially and simultaneously affected the JCI. All shares traded in the Indonesia Stock Exchange indexed by the JCI before LSSR are different from the JCI after LSSR.